2014
DOI: 10.1016/j.matbio.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Decorin deficiency promotes hepatic carcinogenesis

Abstract: Hepatocellular carcinoma represents one of the most-rapidly spreading cancers in the world. In the majority of cases, an inflammation-driven fibrosis or cirrhosis precedes the development of the tumor. During malignant transformation, the tumor microenvironment undergoes qualitative and quantitative changes that modulate the behavior of the malignant cells. A key constituent for the hepatic microenvironment is the small leucine-rich proteoglycan decorin, known to interfere with cellular events of tumorigenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 96 publications
3
77
0
Order By: Relevance
“…From this screen, PDGFR-α/β emerged (Fig. 1B) as a viable candidate to which decorin engages with high affinity and suppresses the formation of HCC [68]. Importantly, these results are congruent with the finding that decorin is suppressed, at the transcriptomic level, in HCC [69].…”
Section: Decorin Structure: High-affinity Interactions With Severasupporting
confidence: 59%
See 2 more Smart Citations
“…From this screen, PDGFR-α/β emerged (Fig. 1B) as a viable candidate to which decorin engages with high affinity and suppresses the formation of HCC [68]. Importantly, these results are congruent with the finding that decorin is suppressed, at the transcriptomic level, in HCC [69].…”
Section: Decorin Structure: High-affinity Interactions With Severasupporting
confidence: 59%
“…Screening the RTKome of two different chemically induced models of hepatocellular carcinoma (HCC), it was found that, in a Dcn null background, many RTKs are constitutively activated [68]. Indeed, the global loss of decorin permits inappropriate, basal activation of several RTKs as measured by an increase in the phospho-Tyr signal.…”
Section: Decorin Structure: High-affinity Interactions With Severamentioning
confidence: 99%
See 1 more Smart Citation
“…Foremost, decorin is a pan-receptor tyrosine kinase (RTK) inhibitor [58, 59] that affects receptor function at multiple levels, including modulation and bioavailability of receptor ligands [60], for tumorigenic and metastatic suppression [6165]. Perhaps the most striking evidence for decorin as “a guardian from the matrix” derives from the observation that decorin deficiency is permissive for tumorigenesis [6668] and increases the basal activity of multiple receptor tyrosine kinases and is further permissive for progression of HCC [69]. Further, as decorin can integrate signaling over multiple receptors including EGFR and IGF-IR, it remains possible that decorin can affect the ERs as well in estrogen responsive breast carcinomas [27].…”
Section: The Instructive Role Of Decorin In Autophagy and Tumorigementioning
confidence: 99%
“…Upregulation of decorin A549 tumor cells resulted in decreased TGF-β1, cyclin D1 expression, and phosphorylation of EGFR, but higher levels of p53 and of p21 (Waf1/Cip1). The changes of these signaling molecules could be correlated with the decreased invasive growth and cell cycle blockage at G1 76,77…”
Section: Ecm Biopolymers and Their Inhibitorsmentioning
confidence: 99%